Any City Could Be Called Universum: About universities, an architectural form and traditions… - Bagina, Elena (project baikal, 2015)
Universities that appeared in different countries at different times have not got any special “university form”. The style paradigm is common for all types of buildings and structures of the same time. If a university has a long history and premises that emerged at different times, it looks more attractive for professors and students than a modern university built from scratch within a short period of time. This makes a university resemble a city. Historical architecture and traditions are a special privilege of famous universities of the world.